2022
DOI: 10.1001/jamanetworkopen.2022.35331
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Preexisting Heart Failure With Reduced Ejection Fraction and Fluid Administration Among Patients With Sepsis

Abstract: ImportanceIntravenous fluid administration is recommended to improve outcomes for patients with septic shock. However, there are few data on fluid administration for patients with preexisting heart failure with reduced ejection fraction (HFrEF).ObjectiveTo evaluate the association between preexisting HFrEF, guideline-recommended intravenous fluid resuscitation, and mortality among patients with community-acquired sepsis and septic shock.Design, Setting, and ParticipantsA cohort study was conducted of adult pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…Reduced cardiac function, which may be caused by a dysregulated response of the host to infection [ 25 ], can exacerbate sepsis, making the clinical management of these patients more complex. Our research indicates that CHF is linked to a higher likelihood of sepsis progression to septic shock, which is consistent with the findings of previous studies [ 26 , 27 ]. Additionally, our study also demonstrated that invasive ventilation increased the risk of deterioration in elderly patients with urosepsis, as previously reported [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Reduced cardiac function, which may be caused by a dysregulated response of the host to infection [ 25 ], can exacerbate sepsis, making the clinical management of these patients more complex. Our research indicates that CHF is linked to a higher likelihood of sepsis progression to septic shock, which is consistent with the findings of previous studies [ 26 , 27 ]. Additionally, our study also demonstrated that invasive ventilation increased the risk of deterioration in elderly patients with urosepsis, as previously reported [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…These data confirmed our hypothesis that more rapid intravenous fluid treatment, as an undifferentiated approach, or even by subtype, is not associated with improved risk-adjusted outcomes in septic shock [ 24 ]. In our model of time to completion of the weight-based intravenous fluid bolus, we did not include patients who received less than a 30 mL per kg bolus and did not assess association between total weight-based fluid volume delivered and mortality.…”
Section: Discussionsupporting
confidence: 85%
“…Our study supports the notion that HF patients may respond differently to fluid resuscitation compared with patients without HF, an inadequately understood but clinically impactful topic ( 27 , 28 ). Patients with HF may receive smaller fluid volumes that are administered more cautiously ( 27 , 29 , 30 ), even in septic shock ( 30 ), due to concerns about iatrogenic volume overload. It is plausible that HF patients have higher mortality and require interventions like mechanical ventilation more often when receiving excessive fluids.…”
Section: Discussionmentioning
confidence: 99%